Collecting and Reporting Mechanism Value Added Tax - Intan Puspanita; Mulyanah Mulyanah; Refi Pratiwi; Aqshal Pratama Yuli Arsya (Journal of Applied Business, Taxation and Economics Research, 2022)
Value Added Tax (VAT) is a tax that is collected and imposed on the delivery of Taxable Goods (BKP) and Taxable Services (JKP). VAT is collected using a tax invoice and a Tax Payment Slip (SSP). Purchases of Taxable Goods are subject to VAT and PKP partners will prepare and submit tax and SSP invoices to the treasurer for the expenditure unit of the Central Office for the Cidanau, Ciujung, and Cidurian River Regions. This study aims to determine the mechanism for collecting and reporting VAT and to find out the obstacles encountered when collecting and reporting VAT at the Work Unit of the Central Office for the Cidanau, Ciujung and Cidurian River Regions. The method used in this research is descriptive with an inductive approach and data collection techniques using observation, interviews and documentation. The results of this study are that the Value Added Tax (VAT) Reporting mechanism carried out by the Expenditure Treasurer at the Work Unit of the Balai Besar for the Cidanau, Ciujung, and Cidurian River Regions is appropriate.